Pseudocapacitive performance of manganese oxide coated hierarchical cobalt oxide structure prepared by hydrothermal process. (August 2017) - Lin, C.-K.; Lin, P.-C.; Shih, S.-J.; Chang, C.-J.; Shi, J.-B.; Chen, C.-Y.
Abstract: In the present study, a manganese (Mn) oxide deposited hierarchical cobalt (Co) oxide structure was prepared as a supercapacitor electrode by a two-step hydrothermal process. A Co-oxide hierarchical structure was first prepared as a template on a graphite substrate by hydrothermal and post heat treatment (calcination) processes. Subsequently, the Mn-oxide was deposited onto the surface of the Co-oxide template to form a Mn-oxide coated hierarchical Co-oxide structure by a secondary hydrothermal process. The effects of calcination time on the material characteristics and pseudocapacitive performance of the Mn-oxide coated structure were investigated. Experimental results showed that the microstructural properties of hydrothermally synthesized Co-oxide with a snowflake-like morphology varied with the calcination conditions. A great improvement of > 100% in capacitance of the Mn-oxide coating was obtained by using a template with a Co-oxide hierarchical structure. Moreover, with high capacitance, the excellent cycling stability of the Mn-oxide coated hierarchical Co-oxide structure exhibited high potential for practical application as a pseudocapacitor.